Hierarchical micro-nanostructured albite-based glass-ceramic for high dielectric strength insulators. Issue 7 (July 2018) - Fuertes, V.; Cabrera, M.J.; Seores, J.; Muñoz, D.; Fernández, J.F.; Enríquez, E.
Abstract: A novel glass-ceramic material based on albite type Na-rich feldspar has been synthesized by conventional ceramic process. High crystallinity, >94% Vol.% is obtained by fast sintering which allows energy saving processing. Albite is the main crystalline phase and tetragonal SiO2 is a secondary phase. Electrical properties were examined by complex impedance, DC measurements, and dielectric breakdown test. Dielectric characterization shows a non-Debye type dielectric behavior with low dielectric constant, 4.6 at 1 MHz, low dielectric losses, (∼10 −3 at 1 MHz, and a large dielectric strength, ∼60 kV/mm), that it is the largest value reported in ceramic insulators. Those dielectric properties are attained by the low glassy phase content in the samples and their unique micro-nanostructure. All these properties make this novel material a very promising candidate in the market of ceramic electrical insulator, highlighting for high-voltage applications.